Indonesian learners in Australian education environment: perceptions, challenges, and resilience - Diana Purwati; Arnis Silvia (Journal of Educational Management and Instruction (JEMIN), 2021)
With the economic development of Indonesia in the recent years, there has been a large number of Indonesian students continue their higher education in overseas countries, particularly Australia. Hence, examining their perceptions, challenges and experiences to adapt to the Australian English learning environment becomes an interesting attribute to explore. Drawing on this issue, the in-hand study explores how Indonesian learners dealt with challenges and difficulties in Australian education environment. Employing a qualitative research, this study involved eight Indonesian learners enrolled in English language programs in a number of Australian universities. Using interview as the instrument, the findings showed that the participants perceived a positive perception toward the communication activities during the teaching and learning practices; however, they encountered some difficulties related to grammar instruction within communicative practice. The results of interview further revealed that most of the learning difficulties they experienced were due to their prior exposure and habit to Indonesian teaching and learning styles. The participants further conveyed that enhancing English ability and building confidence were two most possible ways to deal with the difficulties.Â  These results contribute as fruitful insights for teachers to be aware of different learnersâ€™ styles and needs, particularly those coming from various cultural backgrounds, so that they could engage in more interactive teaching and learning activities.